Hubungan Kemandirian Belajar Dengan Hasil Belajar Matematika Siswa Kelas V SD 2 Singocandi - Natasya Mu’afida, Mutiara; Maulida Nailis Sa’adah; Lisa Noor Amelia; Muhammad Zidan Fakihani; Fitriyah Amaliyah (Universitas Palangka Raya, 2023)
Abstract This study aims to determine the relationship between learning independence and students' mathematics learning outcomes. The method used in this study is a quantitative research method with a correlational design. In this study, researchers used a questionnaire instrument to find out the results of independent learning and the results of daily mathematics tests to find out the results of students' mathematics learning. From the data that has been collected, a correlation test is carried out with the conditions that are the normality test and the linearity test. The results of the analysis of the correlation coefficient between the independent learning variables and student mathematics learning outcomes is 0.948**. Based on the results of the correlation test using SPSS above, the hypothesis that there is a positive and significant correlation between students' learning independence and their mathematics learning outcomes is acceptable. The test results on the normality test using SPSS show that the data is normally distributed. This is indicated by the value of Sig. namely 0.282 and 0.486 where the significance is > 0.05. Based on the results of this study, the higher the student's learning independence, the higher the student's mathematics learning outcomes. And vice versa, when the student's learning independence is low, the lower the student's learning outcomes in mathematics.